Effect of nanoparticles shape on turbulent nanofluids flow within a solar collector by using hexagonal cross-section tubes. (June 2022) - Khetib, Yacine; Abo-Dief, Hala M.; Alanazi, Abdullah K.; Sajadi, S. Mohammad; Kalbasi, Rasool; Sharifpur, Mohsen
Abstract: This paper investigates the turbulent flow of nanofluid (NFs) in which boehmite-alumina nanoparticles with different shapes of platelet, brick, blade, and cylinder suspended in a mixture of W/EG in a flat plate solar collector (FPSC). A hexagonal cross-sectional tube is used in the FPSC and compared with a simple one. The problem variables include flow rate (FR) (0.25–1 kg / s), shape and volume percentage (φ) of nanoparticles (NPs) (0–4%), tube shape (circular and hexagonal) and FPSC material (copper and steel). The influence of these variables on the FPSC output temperature (TCOUT ), Nusselt number (Nu) and heat transfer coefficient (h) is investigated. The results reveal that copper FPSC can provide higher TCOUT but has lower convective coeffient and Nu than steel FPSC. The outlet fluid temperature is 1.86 °C higher when pure fluid flows in copper tubes. The addition of NPs, particularly bricks, causes the temperature of the fluid at the outlet to rise. This increase is about 1°for φ = 4%. The use of a hexagonal tube enhances the temperature of the fluid at the outlet relative to a circular one. For copper and steel FPSCs, this increase is 2.67 and 1.75 °C for pure fluid, respectively. The addition of NPs reduces the amount of heat transfer and Nu for the FPSCs.